Strategic entrepreneurship and the growth of the firm: the case of Taiwan's bicycle industry. (25th January 2008) - Yan, Ho-Don; Hu, Mei-Chih
Taking advantage of the modular product architecture in the global bicycle industry, Taiwan has created a unique industry organisation that has allowed the island to become a bicycle production powerhouse. We stipulate four characteristics of Taiwan's bicycle industry for this success: parallel networking, abundant entrepreneurial firms, supportive government and close ties with the USA and Japan. In the case study of Giant Bicycle Corporation, we integrate the entrepreneurship perspective with strategic management to explain the wealth creation and the growth of the firm. With strategies on internal organisation reengineering and global deployment, Giant has been able to build up its sustainable competitive advantages. We conclude that entrepreneurship is the key element for the growth of the firm and even a labour-intensive or non-high-technology industry can be selected as a development strategy.